Strategi Menghadapi Kecemasan pada Single Mother di tengah Pandemi Covid-19 - Fifi Dwi Mileniasari; Rodlotul Janah Amalia Rachma Ajeng; Ali Syahidin Mubarok; Retno Sulistyaningsih (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
The occurrence of the Covid-19 pandemic made whole sectors experience extraordinary disruption. The economic sector was the worst part because it must be stopped as a result of the pandemic. This pandemic has also made everyone anxious because of exposure to covid-19. Many people lose their jobs, and even single mothers are no exception. Single mother position is not only as a breadwinner, but also as parent carrying a heavy burden especially when she loses their job. The anxiety increases because of her position and condition. Furthermore, single mother was increasingly concerned if she had been exposed to covid-19 and she has no medical expenses. This research was a qualitative research with a case study approach. Data collecting used observation and semi-structured interviews. The number of subjects in this study were two people. The results of this study were that both subject 1 and 2 had anxiety about the spread of the virus. Both subjects had economic anxiety which was at the intermediate level. Subjects 1 and 2 prefer to surrender to what had happened due to this pandemic, especially economic problems. Subjects 1 and 2 worked as best they could to face the economic conditions of the family. Subject 1 and 2 used religious coping for survival strategy facing Covid-19 pandemic.